The Fashionable Muslim - Gopi, Dallas Raj (Auckland University of Technology, 2010)
The Fashionable Muslim is a story about pragmatism, but not obviously so. It’s also a story about how too much is choice as opposed to too little choice can be a major cause of scepticism.
Keywords: Muslim; Multi-culturalism